STRATEGI KOMUNIKASI POLITIK TIM PEMENANG HAMARTONI ROMLI PADA PILKADA 2024 DI KABUPATEN LAMPUNG UTARA - Okta Irjun Saputra; Anna Gustina Zainal; Ibrahim Besar; Nanda Utaridah; Nanang Trenggono (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
The regional head election (Pilkada) is a crucial democratic process in determining local leadership. This study aims to analyze the political communication strategy of the Hamartoni-Romli campaign team during the 2024 local election in North Lampung Regency. This research employs a descriptive qualitative approach, using Dan Nimmo’s political communication theory, which highlights five key elements: communicator, message, media, audience, and effect. Data were obtained through in-depth interviews, campaign observation, and documentation of social media content and public communication materials. The results indicate that the campaign team established a well-structured communication system, segmented voters by demographic and geographic factors, and utilized a hybrid media strategy combining digital platforms such as TikTok and Instagram with local media and face- to-face approaches. The campaign messages were emotionally and contextually framed, focusing on integrity and alignment with grassroots communities. The candidate actively contributed to message framing and communication planning. Routine evaluations were conducted to respond to field dynamics, including political attacks and the spread of hoaxes. This strategy proved to be participatory, adaptive, and data-driven, effectively enhancing voter engagement and building a positive image of the candidate among the public.